Hegemony and socialist strategy : towards a radical democratic politics - Laclau, Ernesto (Verso, 1985)
To what extent does it call into the question the idea of social totality that underpinned Marxism and many other socialist theories? Does the concept of hegemony imply a new logic that goes beyond the essentialism of classical Marxist thought? These are some of the questions that this now seminal book attempts to answer. It traces the genealogy of the present crisis, from the nineteenth-century debates to the contemporary emergence of new forms of struggle, making it a classic text both for understanding hegemony and for focusing on present social struggles and their significance for democratic theory.